Pengembangan E-modul Berbasis Project Based Learning Menggunakan Flipbook Pada Mata Pelajaran Pemeliharaan Sasis dan Pemindah Tenaga Kendaraan Ringan - Rahmi, Salsabila Tri; Anreski, Vanny; Purwanto, Wawan; Wakhinuddin, Wakhinuddin; Wulansari, Rizky Ema (PAKAR Pendidikan, 2023)
Vocational secondary education institutions are able to anticipate and manage change by using various existing skills by utilising technology. Improving teaching media is one way to utilise technology. Learning media in the form of electronic modules must be developed in vocational high schools. The main problem that occurs, the demands of the K13 curriculum regulations require schools to use Project Based Learning with insufficient learning resources, insufficient learning resources and Students have difficulty in applying existing concepts to the tasks given, have poor problem solving skills, have stunted critical thinking skills of students. Overcoming these problems, the real task is to support people with skills to improve the existing learning process. The objectives obtained from this study based on the formulation of the problem: to produce a valid, practical and effective learning module. The 4D Research and Development model was chosen which consists of four phases, namely the defining, design, development and implementation phases. The results of the development research in the form of project-based learning e-modules on Maintenance of Chassis and Power Transfer of Light Vehicles are valid with the test results of each aspect of the first aspect of the material 0.81 second aspect of the grammar aspect 0.85 third aspect of the description of the fourth material self-instructional 1, practical with the test results of each aspect of the first aspect of the content 93% second aspect of use 94% third aspect 89% and effective with the results of the gain score test 0.7 used to improve student learning outcomes.